PENGARUH KEPEMIMPINAN, KREATIVITAS DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA CV ALFA GROUP MEDAN - Girsang, Maranata; Tinambunan, Anitha Paulina (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
This study aims to determine the effect of leadership, creativity, organizational culture on the performance of employees CV. Alfa Group Medan. The total population of this study is 35 people and the number of samples through the census is 35 people. The analysis technique used in this study is multiple liner regression. Descrptive analysis and hypothesis testing.he results of this study indicate that the variable leadership, creativity, organizational culture have a positive and significant effect on the performance of employees CV. Alfa Group Medan. Creativity is the most dominant influence on performance of employees CV. Alfa Group Medan. The coefficient of determination (R Square) of 0.473 means that employee performance can be explained by leadership, creativity, organizational culture by 47.3% while another 52.7% can be explained by other variables that are not included in this study such as discipline and commitment.